Національні мотиви у декорі костюмів у творчості Марти Токар (на прикладі діяльності Львівського будинку моделей) - Костельна, М. (Народознавчі зошити, 2013)
Contemporary Ukrainian designers of fashion quite often turn their attention to the usage of national cultural motifs and folk art, so fine as decorative applied ones. That’s why in the following article some preconditions for specified use of ethnical styling in the works of Ukrainian designers have been considered and exemplified by creations of Martha Vasylivna Tokar, a Lviv fashion house artist. Particularly, there has been performed an analysis of Martha Tokar’s creative search in the context of Ukrainian national costume traditions of various ethnographical regions; the meaning of mentioned phenomena for further development of modeling art in Lviv during the 2nd half XX c. has been defined and presented.